Review on AC-AC Converter Based Dynamic Voltage Restorer - Tamilvanan G.; Mahendran S. (Institute of Advanced Engineering and Science, 2016)
The maintain power quality is one of the major part of all kind of industry as well as power systems. Voltage sag and voltage swell the common power quality issue. The Dynamic Voltage Restorer is the common Device which is used to mitigate the above problems. In this paper provides review on various type of AC-AC converter based DVR. The use of AC-AC converter can compensate the voltage sag and swell without need of any kind of storage elements like capacitor and batteries. The absence of storage elements can reduce size and weight of the DVR. The feature various type of AC- AC converters based DVR is concentrated in this paper.